New results on egalitarian values for games with a priori unions. (4th March 2023) - Gonçalves-Dosantos, J. C.; Alonso-Meijide, J. M.
ABSTRACT: Several extensions of the equal division value and the equal surplus division value to the family of games with a priori unions have been proposed by Alonso-Meijide et al. [On egalitarian values for cooperative games with a priori unions. TOP. 2020;28:672–688]. In this study, we provide new axiomatic characterizations of these values. Furthermore, using the equal surplus division value in two steps, we propose a new coalitional value. The balanced contributions and quotient game properties generate a different modification of the equal surplus division value.